G530(P) Do young people with epilepsy disengage with healthcare following transition to adult services?. (25th October 2020) - McInally, J; Kirkpatrick, M
Abstract : Introduction: There is a concern that young people wit epilepsy will disengage with healthcare following transition to adult services. The aim of this review was to identify from the medical literature any evidence to support or refute these concerns. Methods: Markers of engagement were identified as scheduled care attendance, unscheduled care attendance, medication adherence, mortality, healthcare costs and health behaviours. A literature review was carried out for each of these areas. Studies published in the period 2008–2018 were included. Results: There is good evidence that there is no increase in emergency care use in young adults with epilepsy compared to children or older adults. There are no studies comparing scheduled care use by children, young people and older adults. There is evidence that young people with epilepsy attend their GP twice as frequently as age matched peers, but it is unclear how much of this is related to epilepsy and how much to co-morbidity. There is conflicting evidence around medication adherence and therefore no conclusion can be drawn as to whether transition has an impact on this. Young adults with epilepsy have higher rates of unexpected death than children or older adults. They are more likely to have uncontrolled epilepsy than older adults. In a deprived population, death by accident is more likely in adults with epilepsy. People with childhood epilepsy have been found to have a lower level of education than age matched controls, as well as higher unemployment levels and increased reliance on state welfare programmes. Conclusion: There is a paucity of evidence to show whether or to what extent young people with epilepsy disengage with healthcare following transition to adult services. There is no evidence that young people have different scheduled care attendance or medication adherence following transition. There is good evidence that young adults do not have higher emergency care attendance or admissions to hospital. There is evidence that young people have an increased risk of unexpected death around the time of transition and this should be addressed.